BROTHEL OF TU BA – THE INTENSE PERIOD OF THUY KIEU’S LIFE - Nguyễn Hữu Sơn (Tạp chí Khoa học Đại học Đà Lạt)
We apply gender theory to understand the life of Thuy Kieu at the brothel of Tu Ba in relation to her entire life. We focus on analyzing memories, reflections, and pure love predictions in contrast to the days of exile at Tu Ba's brothel. We identify the levels of spiritual life, emotions, and sexual behaviors in relation to real situations, emotions, psychology, and human values. Expanding our comments, we discuss some opinions of Nguyen Bach Khoa, Ho Dac Duy, and Phan Que in explaining instinctive characteristics, humanity, and social conventions. The reality of action and the ability to self-sense about sexual acts shows the personality, bravery, and cultural depth as well as the rich spiritual world of Thuy Kieu. The article investigates, verifies the reality and the ideal, identifies the multi-personality characteristics of Thuy Kieu from the measure of instinct and individual human qualities, and contributes to affirm the creative talent of the great poet, Nguyen Du.